STUDY OF FUNCTIONS, MOTIFS, AND SYMBOLIC MEANINGS OF TOBA BATAK ULOS SADUM WOVEN FABRICS IN NORTH SUMATRA - HARIANI, ELIZABETH; KUSUMASTUTI, ADHI (Fashion and Fashion Education Journal, 2023)
Abstract. Ulos sadum is a Batak woven fabric that was originally known in Angkola/South Tapanuli as a symbol of joy with its characteristic red color and festive floral motifs that have cultural significance through the Batak tradition, and can contain magical, religious, love, unity and prayer values. The development of the times has an impact on the ulos phenomenon is not used in accordance with the function, motifs and meaning of ulos because it is starting to erode and can threaten the extinction of the ulos which makes people worry, especially for the Toba Batak sphere. This study aims to examine the functions, motifs, and symbolic meanings contained in the Toba Batak ulos sadum. This research is a type of qualitative research. The approach used is semiotics. The sources of data in this study were ulos weavers, experts in the field of ulos (ulos observers, ulos business actors, lecturers of cultural studies), literature, and ulos. Data collection techniques used are literature studies, observations, interviews, and documentation. The data analysis technique used is the theoretical data analysis of Miles and Huberman namely data reduction, data presentation and conclusion/verification. The results showed that the function of the Toba Batak personal sadum was to be used by women as ulos holong (love), a symbol of joy and prayer for the wearer or daughters who are currently married, and to show the beauty of women from their work. The physical function is for scarves, long cloths/slings, back cover and gifts. The social function is for happy and sad events such as mangulosi , house inauguration, baptisms, child births, church birthdays and funerals. The function of the community in the past was that it was used for daily activities, scarves and traditional events. The function in today's society is still the same as before but has been modernized, namely the development of sadum patterned fabrics into souvenirs such as wall hangings, tablecloths, bags, clothing, skirts, accessories and others. Some sadum motifs come from Dutch and India acculturation. The motifs describe animals and nature in the Batak land. The distribution of motifs on the Toba Batak ulos sadum is Toba Silindung, Toba Samosir, Toba Holbung/Uluan and Toba Sitolu Huta. The overall symbolic meaning contained in the Toba Batak ulos sadum, namely the joy and social relations of humans and the surrounding nature is translated from the meaning contained in each motif that forms a single unit. This cloth in custom is called ulos holong (love), which expresses affection, joy and prayer to give dynamism to the community.